Dynamic Changes in the Gut Microbiota and Metabolites during the Growth of Hainan Wenchang Chickens - Yingzhi He; Jie Li; Feifan Wang; Wei Na; Zhen Tan (Animals, 2023)
Gut microbiota and their metabolites play important roles in animal growth by influencing the host’s intake, storage, absorption, and utilization of nutrients. In addition to environmental factors, mainly diet, chicken breed and growth stage also affect changes in the gut microbiota. However, little research has been conducted on the development of gut microbiota and its metabolites in local chickens. In this study, the cecal microbiota and metabolites in different developmental stages of Hainan Wenchang chickens (a native breed of Bantam) were investigated using 16S rRNA sequencing and untargeted metabolomics. With aging, the structure of gut microbiota tended to be more stable. The relative proportions of dominant bacteria phyla Firmicutes, Bacteroidetes, and Proteobacteria showed stage changes with the development. With aging, gut microbiota and their metabolites may have structural and functional changes in response to nutrient metabolism and immune requirements in different physiological states. Several microbial and metabolic biomarkers with statistical differences were detected in different development stages. The bacteria that form networks with their significant related metabolites were different in various growth stages, including uncultured_bacterium_f_Ruminococcaceae, Ruminococcaceae_UCG-014, Faecalibacterium, uncultured_bacterium_o_Bacteroidales, and uncultured_bacterium_f_Lachnospiraceae. Partially differential bacteria were significantly correlated with short-chain fatty acids such as butyric acid. These findings may provide new insights into the physiological and molecular mechanisms of developmental changes of local chicken breeds, as well as resources for microbial and metabolic biomarker identification to improve growth efficiency.